The CD performance progression tool - Hollings, S.; Hume, P.; Hopkins, W. (New Studies in Athletics, 2012)
In 1997 two of the authors created a method to compare performance progression in track and field athletics using tables, published in booklet form, plotting the progressions of 390 successful athletes. Such a tool is useful for coaches and high-per-formance support programme managers as it gives a basis for determining if an athlete is on a course that will lead to world-class results or if adjustments to the athlete's preparation and targets are required. However, at the time the original work was published certain limitations were identified. The methodology was subsequently adopted by both UK Athletics (in 2006) and Athletics New Zealand (in 2009) to produce a series of "performance funnels" to monitor both their elite and developing athletes. In the process, the two organisations addressed some but not all of the identified weaknesses. This article outlines how a revised method was developed using a database of 168,000 performances from more than 2,000 athletes. The new method has been turned into a computer-based tool available on a CD. The article explains the use of the tool and provides interpretations of data from example athletes.